Corporate Email Management Policy: How to Improve Digital Communication - Castro, Joaquim; Terra, Ana Lúcia (Bobcatsss, 2023)
The purpose of this paper is to explain the specifics of email as corporate mail and to underline some of the main transformations that it has allowed to organizational communication and the challenges to information management in professional contexts. The need to create an email management policy defining usage rules, in order to overcome some administrative, ethical, legal and economic problems or the loss of organizational memory will be emphasized. A set of documents produced by five archival national agencies, from Brazil, Canada, South Africa, United Kingdom, and USA, will be analysed in order to define the main topics that should be considered in any corporate email management policy. The five documents will be presented comparatively using an analysis grid. As an output of the content analysis from these national documents on email management policies, a set of recommendations about the main topics to be included in a corporate email management policy will be presented.